Wide-area oscillation damping in low-inertia grids under time-varying communication delays - Alghamdi, Sultan; Markovic, Uros; Stanojev, Ognjen; Schiffer, Johannes; Hug, Gabriela; Aristidou, Petros (My University, 2020)
Wide-Area Control (WAC) can be efficiently used for oscillation damping in power systems. However, to implement a WAC, a communication network is required to transmit signals between the generation units and the control center. In turn, this makes WAC vulnerable to time-varying communication delays that, if not appropriately considered in the control design, can destabilize the system. Moreover, with the increasing integration of renewable energy resources into the grid, usually interfaced via power electronics, power system dynamics are becoming drastically faster and making WAC more vulnerable to communication delays. In this paper, we propose a design procedure for a delay-robust wide-area oscillation damping controller for low-inertia systems. Its performance is illustrated on the well-known Kundur two-area system. The results indicate that the obtained WAC successfully improves the oscillation damping while ensuring robustness against time-varying communication delays.
Keywords: Low-inertia systems; Oscillation damping; Time-varying communication delay; Wide-area control